KAJIAN AWAL KATALIS HARGA RENDAH UNTUK PRODUKSI DIMETIL ETER SECARA LANGSUNG DARI SYNGAS BATUBARA - Bhakti .; Zulaicha .; Joni .; Galuh .; Nurdiah .; Tyas . (Jurnal Ilmiah Teknik Kimia, 2017)
Coal utilization including its processing for an alternative energy is quite large in Indonesia and absolutely necessary. Especially on coal with low calorific value like lignite, at handling with direct combustion as in conventional coal power plant is an environmentally friendly manner because its emission contains harmful substances NOx and CO. Approching with clean coal technologies, gasification, emissions of harmful substances into the environment can be reduced. This gasification process, coal is converted into syngas which is an intermediate product that can be directed into various types of alternative fuels such as methanol. Development of efficient and low cost DME synthesis from syngas produced from gasification of coal has been our interest, in particular development  of low cost catalyst which is shown by Low Pressure Fixed Bed Reactor. In this research scheme, we develop the catalyst using Co-precipitation method and Copper based catalyst. In this preliminary study, the DME synthesis of catalysts based on Methanol catalyst has been modified by combined it with HZSM-5 as dual catalyst. This process will perform DME production in one step Fixed Bed Reactor. micromeritic reactor at mild operating condition. The results of modified catalyst to Sud-Chemie/NaHZSM-5 Si/Al 25 showed that DME synthesis at 30 bar and 270oC reach a good conversion, up to 0.9% and predicted still able to increase. Keywords: low rank coal, DME synthesis, low cost catalyst, low pressure fixed bed reactor